The Subject of Baptism in the Latin Church and Pope Francis’ Pastoral Call for Sacramental Openness - Lipińska, Weronika (Prawo Kanoniczne, 2025)
From the outset, Pope Francis' pontificate has been marked by a clear message of openness, mercy and closeness of the Church to all people, regardless of their life circumstances. A particular expression of this pastoral sensitivity can be found in his appeal that baptism should not be denied to anyone who requests it. In the face of dynamic social, cultural and religious changes, contemporary pastoral practice has faced new challenges that call for a reflection on how to implement this papal vision. At the same time, the Church remains faithful to its traditions and norms of canon law, which define the conditions for receiving the sacraments. This has raised the question of whether and how the openness advocated by the Pope can be reconciled with the normative legal framework and the realities of pastoral ministry. The analysis shows that: canon law does not exclude the possibility of administering baptism to individuals but leaves room for pastoral discernment; a request for baptism, even if it does not meet all the formal requirements, can be the beginning of a path to conversion and spiritual growth; and the Church's modern mission requires the integration of theological requirements with pastoral flexibility. Pope Francis' appeal thus finds its practical justification not only in the Church's mission, but also in its deepest identity. A Responsible openness to the request for baptism is not only possible, but even necessary if the Church is to remain faithful to its mission of proclaiming the Gospel to all people.